2016
DOI: 10.1186/s13104-016-2170-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of Corynebacterium xerosis isolated from a sheep cutaneous abscess: first case report in Mexico

Abstract: BackgroundCorynebacterium xerosis is a commensal organism found in skin and mucous membranes of humans. It is considered an unusual pathogen, and it is rarely found in human and animal clinical samples. Here we describe the isolation of C. xerosis from a 4-months-old Pelifolk lamb located in Tesistán, central western Mexico. This microorganism should be considered for differential diagnosis in cutaneous abscessed lesions in sheep, as it represents a zoonotic risk factor for human infection in sheep farms.Case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In human, Corynebacterium amycolatum and Corynebacterium striatum which were identified in this study, have been implicated in bacteraemia, endocarditis and in acute/chronic complicated skin and soft tissue infections [2], [10], ear infection [8] and corneal ulcer [9]. Also, Corynebacterium xerosis isolated in this present study is among the most frequently reported coryneform bacteria causing infections in human [6], [20].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In human, Corynebacterium amycolatum and Corynebacterium striatum which were identified in this study, have been implicated in bacteraemia, endocarditis and in acute/chronic complicated skin and soft tissue infections [2], [10], ear infection [8] and corneal ulcer [9]. Also, Corynebacterium xerosis isolated in this present study is among the most frequently reported coryneform bacteria causing infections in human [6], [20].…”
Section: Discussionsupporting
confidence: 61%
“…Reference [5] was the first to report the isolation and identification of Corynebacterium xerosis from animal clinical specimens in Spain. Similarly, Reference [6] reported for the first time the isolation and molecular characterization of Corynebacterium xerosis from a clinical sample of an ovine cutaneous abscess in Mexico. Strains of Corynebacterium bovis and Corynebacterium amycolatum were respectively isolated from milk samples from clinical bovine mastitis and sub-clinically infected bovine quarters [7].…”
Section: Introductionmentioning
confidence: 99%
“…hanseni (absent from group B) – microorganisms that could be isolated from wounds and pus respectively [ 72 , 73 ]. It is also noticeable that Corynobacterium xerosis , described as isolated mostly from subcutaneous lesions in swine, occurred in our study most frequently in sows fed with garlic extract [ 74 ]. In turn, in association with probiotics we noted a higher prevalence of Corynebacterium puruviciproducens , bacteria which exhibits immunomodulatory properties and can stimulate hosts humoral immune response to pathogenic microorganisms by adjusting the function of macrophage [ 75 ] .…”
Section: Discussionmentioning
confidence: 93%
“…It is negative to casein and starch hydrolysis, citrate, mannitol salt agar and methyl red. This organism has been isolated from poultry animals [8,9].…”
Section: Corynebacterium Xerosis Is An Aerobic At 37mentioning
confidence: 99%